How much variation is in the shape of fossil pupation chambers? An exploratory geometric morphometric analysis of Fictovichnus gobiensis from the Late Eocene of Oaxaca, southern Mexico - Guerrero-Arenas, Rosalía; Zúñiga Marroquín, Tania; Jiménez-Hidalgo, Eduardo (Sociedad Geológica Mexicana, 2018)
Shape is one of the characteristics most often used for the identification of ichnotaxa. Several studies have demonstrated the potential of geometric morphometrics in ichnology, in order to distinguish the nature of the tracers’ producers. In this study, we used geometric morphometrics to analyze variation of shape in Fictovichnus gobiensis, a fossil pupation chamber produced by Coleoptera. The objective of this study was to analyze diverse clusters of similarly shaped pupal chambers, indicative of several coleopteran producers. The 42 analyzed specimens were collected from late Eocene-aged outcrops in the surrounding areas of Santiago Yolomécatl, northwestern Oaxaca, where these fossil traces are relatively abundant. On the specimens, 2 landmarks and 34 semilandmarks were placed for 2-dimensional Cartesian coordinates. Shape variation was analyzed with Procrustes distances as a measure of similarity. Unweighted Pair Group Method with Arithmetic Mean method was used for cluster analyses, and Principal Component Analysis and Canonical Variates Analysis were used to explore shape variety and differences between the clusters. The elliptical shape of the chambers is variable, but it was possible to group and distinguish 4 main morphs, suggesting 4 potential producers. Morphs recognized in this study represent indirect evidence of beetle diversity that were not directly preserved in the fossil record. Future analyses in pupal chambers of recent Coleoptera could clarify the nature of the producers. Additional research could establish if more morphs exist in larger samples from Yolomécatl localities.
Keywords: Cámaras pupales; Fictovichnus gobiensis; Oaxaca; Coleoptera